O005/#638 ProMisE-2: a one step DNA-based endometrial cancer molecular classifier. (4th December 2022) - Jamieson, Amy; Lum, Amy; Leung, Samuel; Thompson, Emily; Senz, Janine; Talhouk, Aline; Bashashati, Ali; Huntsman, David; Mcconechy, Melissa; Mcalpine, Jessica
Abstract : Objectives: Despite recommendations for the integration of molecular classification in endometrial cancers (EC) into pathology reporting and clinical management, uptake is inconsistent. To assign ProMisE subtype, all molecular components must be available (POLE mutation status, MMR and p53 immunohistochemistry (IHC)) and often components are performed at different stages of care and/or at different centers resulting in diagnostic delays. We assess the performance of a one step DNA-based molecular classifier (ProMisE-2) compared to ProMisE. Methods: DNA was extracted from ECs that had previously undergone molecular classification using ProMisE (POLE sequencing, IHC for p53 and MMR). ProMisE2 was derived using the Imagia Canexia Health Find It next-generation sequencing assay to assess mutations in POLE, TP53 and presence of microsatellite instability (MSI). Molecular subtypes assigned by ProMisE and ProMisE-2 were assessed for concordance metrics and the ability to recapitulate Kaplan-Meier survival curves. Results: ProMisE-2 was assessed in 91 ECs with 2 cases failing sequencing coverage thresholds. 85/89 of cases were concordant with a kappa statistic 0.93 and an overall accuracy of 0.96. Five of six cases where ProMisE-2 was performed on matched biopsy and hysterectomy specimens were concordant. Molecular subtype assignment was associated with outcomes (PFS, DSS, OS) in both ProMisE and ProMisE-2 ( figure 1 ). Conclusions: We demonstrate high concordance of a one step DNA-based EC molecular classifier when compared to the original ProMisE classifier, importantly maintaining the prognostic value of ProMisE and presenting an option for centers where routine MMR and p53 IHC are not performed. Further validation is needed before implementation into clinical practice.